The Correlation Between Self-Confidence and English Speaking Achievement of the Secondary School Students - Putrika Oktaria (Jurnal Pendidikan Dasar dan Menengah, 2023)
In the foreign language (FL) learning process, self-confidence is also important especially when speaking the language because self-confidence is the basis of student motivation to attain a success of FL learning. In fact, some students still feel afraid and not confident when learning English, especially in speaking English. One of their fear is afraid of being laughed by their schoolmates. These problems then make students inactive in the FL learning process. So, they do not want to participate either to ask questions, answer questions from the teacher and also express opinions to talk in classroom interaction. The objective of this study is to examine the correlation between students’ self-confidence and English speaking achievement of the secondary school students. The method used in this study was correlational research design. Samples were taken by purposive sampling technique. There were 37 students (18 male students and 19 female students) taken as the sample who were in the tenth graders of high school. To collect the data, the researchers used a questionnaire to measure students' self-confidence, and they also used a speaking test by a speech monologue made by students to determine speaking achievement. The results show that the correlation between self-confidence and English speaking achievement is r=0.346 and p<0.05 which means there is a positive correlation between both variables.